الفكر التنموي في مضامين الاتصال الجماهيري -دراسة تحليلية نقدية لعينة من برامج إذاعة الوادي- - حجاجي رشيدة (université d'eloud, 2026)
الملخص: أهداف الدراسة: • تحليل المضامين التنموية للإذاعة المحلية للوقوف على ما يتم عرضه من فكر تنموي ومدى تناسبه مع خصوصية البيئة المحلية. مع الوقوف على أوجه القصور في كيفيةمعالجتها لمختلف القضايا التنموية • تهدف الدراسة إلى تقديم رؤية علمية نقدية حول مضامين البرامج التنموية الإذاعية لرصد الوعي الذي تشكله نحو قضايا التنمية، والتعرفعلى توجهها الإيديولوجي وسياستها التحريرية. • إبراز أهمية التخطيط الإذاعي التنموي على المستوى المحلي وعلاقتهبالنهوض بالإستراتيجيات التنموية وتطلعات المجتمع المحلي. أسئلة البحث: * هل البرامج التنموية التي تبثها الإذاعة المحلية بالوادي تحمل فكرًا تنمويًا محليًا؟ * هل التخطيط الإذاعي للبرامج التنموية يتناسب مع ماتتطلبه البيئة المحلية من تنمية؟ * ماهي الآليات المتبعة في عرض البرامج التنموية بالإذاعة المحلية بالوادي لتحقيق مشاركة فعلية بينجميع الفاعلين بالمجتمع المحلي السوفي؟ الفرضيات: الفرضية الأولى:تبث الإذاعة المحلية بالوادي فكرًا تنمويًا محليا بكل أبعاده الاقتصادية والاجتماعية والبيئية. الفرضية الثانية:التخطيط الإذاعي للبرامج التنموية التي تعدها الإذاعة المحلية بالوادي مرهون بالتخطيط المركزي للإذاعة الوطنية لتنمية المجتمع المحلي. الفرضية الثالثة:تعتمد الإذاعة المحلية بالوادي على البرامج التفاعلية في عرض الفكر التنموي المحلي بين مختلف الفاعلين (الجمهور، المتخصصين، الهيئات) لضمان مشاركة فعلية في العملية التنموية. المقاربة المستعملة: تم تبني في هذه الدراسة النظرية النقدية، حيث تم استخدام كل من المقاربة النظرية "لببير بورديو" "الممارسة الاجتماعية" والمقاربة النظرية "ليورغن هابرماس" "الفعل التواصلي". مجال الدراسة: المجال المكاني: تم إجراء الدراسة الميدانية بالإذاعة المحلية بالوادي. المجال الزماني:استغرقت الدراسة قرابة ثلاث سنوات ونصف بين النظري والميداني، وكانت البداية مع الدراسة المفاهيمية والقراءات عن موضوع بحثنا سنة 2022.وبعد الإطلاع على الأدبيات والقراءات استلزم الأمر النزول للميدان والقيام بالجولة الاستطلاعية. أما الدراسة الميدانية بدأت فعليًا من جانفي 2024. العينة: وفي دراستنا الحالية تم اختيار وبأسلوب العينة القصدية غير الاحتمالية الدورة الإذاعية المكونة من ثلاثة أشهر (ديسمبر2023، جانفي، فيفري 2024)،وباعتبار أن الدورة الإذاعية لثلاثة أشهر تتضمن كل من البرامج التنموية،الترفيهية،التثقيفيهية،الرياضية والإخبارية،استلزم الأمر اختيار وبأسلوب قصدي البرامج التنموية فقط والتي تمثلت في هذه الدراسة بخمسة برامج،كل برنامج يتكون من مجموعة من الأعداد تم بثها خلال فترة الأشهر الثلاثة المختارة. المنهج المتبع في الدراسة: اقتضت طبيعة البحث السير على المنهج المختلط وهومزيج بين منهجين الكمي والكيفي وهوطريقة منهجية يتم فيها جمع ودمج كل الأساليب الكمية والكيفية بدراسة واحدة. التقنيات المستعملة: تم استخداماستمارة تحليل المحتوى كأداة رئيسة في البحث، مستعينةً بكل من أداة المقابلة والملاحظة كتقنيات مدعمة للتحليل. نتائج الدراسة: • تنحاز الإذاعة المحلية بالوادي من خلال ما تبثه من برامج تنموية لمواقف وإيديولوجية السلطة ولا تراعي الواقع المحلي السوفي، فهي تعمل على تغييب وعي المواطن المحلي وتزييفه بهدف الحفاظ على الوضع القائم واستقراره. • لا تعرض الإذاعة المحلية بالوادي وجهات النظر المختلفة بصفة متوازنة في معالجتها للمواضيع التنموية المطروحة، فهي تستضيف ضيوف متنوعين إلا أن تعاملهم مع المواضيع المطروحة يخضع لأجندات معينة، وهي بذلك تقع في إشكالية الانحياز إلى موقف معين. • لا تملك الإذاعة المحلية بالوادي هيئة إعلامية متخصصة في معالجة القضايا والموضوعات التنموية والتي بإمكانها تقديم دراسات وبرامج تنموية تراعي خصوصية البيئة المحلية. • لا تشهد الإذاعة المحلية بالوادي تخطيطًا محليًا لبرامجها التنموية، فالتخطيط الإذاعي مبرمج من الأعلى (الإذاعة المركزية) إلى الأسفل (الإذاعة المحلية)، وهنا القائم بالاتصال يجد نفسه مقيدًا وخاضعًا للإدارة المركزية وهذا ما يمنعه من التعرض للموضوعات التي تهم مجتمعه المحلي. • لا تولي الإذاعة المحلية أهمية للتغذية الراجعة، وهذا ما عكسه عدم اعتمادها على الجمهور المحلي كمصدر للمعلومة وعدم فتحها لقنوات الحوار والتفاعل في برامجها التنموية وهذا ما أعاق المشاركة الفعلية لذلك الجمهور في التخطيط والتنفيذ للبرامج التنموية. Résumé :فرنسية أو انجلزية Aims of the study: the study aims at: • Analyzing the developmental contents of the local radio in order to identify the programs broadcasting developmental thinking and know whether they fit with the specificity of the local environment, and to identify their deficiencies in dealing with the various developmental questions; • Providing a scientific and critical perspective on the developmental contents of the radio programs to assess the extent to which they raise awareness of the developmental questions, and to identify their ideological attitude and editorial policy; • Highlighting the importance of developmental radio planning at the local level, and its relationship with the promotion of the development strategies and the aspirations of the local community. Questions of the study • Do El-Oued Local Radio’s developmental programs carry a developmental thinking? • Does the developmental programs’ radio planning meet the developmental expectations of the local environment? • What mechanisms are adopted by El-Oued Local Radio to broadcast developmental programs in order to ensure an active involvement of all the local Soufi community actors? Hypotheses First hypothesis: El-Oued Local Radio broadcasts a local developmental thinking with all its economic, social and environmental perspectives. Second hypothesis: Theradio planning of El-Oued Radio developmental programs relies on the central planning provided by the National Radio aimed at promoting the local community. Third hypothesis: El-Oued Local Radio relies on interactive programs in the broadcasting of local developmental thinking among the various actors (public, specialists, bodies) to ensure an active involvement in the development process. Approach This study adopted a critical theory following Pierre Bourdieu’s theoretical approach “Social Practice” and Jurgen Habermas’s theoretical approach “Communicative Action”. Scope of the Study Space : the field work was carried out at El-Oued Local Radio. Time: the study was carried out in about three years and half a year. During this period of time, both the theoretical work and the field work were done. It started in 2022 with concept study and theme-related readings. Upon review of related literature and readings, the author began the field work and the exploration. The field work effectively started in January 2024. Sampling Following the non-probability purposive sampling method, the three-month broadcast period, ranging from December 2023 to February 2024, was chosen to be the study sample. During this three-month period, developmental, entertaining, sports and news programs were broadcast. However, for the requirements of the research, only developmental programs were purposively chosen. In this study, five programs that were broadcast during the aforementioned period, with a number of episodes for each program, were chosen. Research Method To conduct this research, a mixed method was followed. This is a combination of both qualitative and quantitative research methods. It is a method that allows the gathering and integration of all the qualitative and quantitative research designs in a single study. Research tools This research was carried out using a content-analysis, as the main research tool. To support the analysis, an interview and an observation were also used in this research. Results of the Study • El-Oued Local Radio’s developmental programs indicate the radio’s bias towards the authority’s attitudes and ideology, and does not take into account the local reality of the Soufi community. It ignores and falsifies the local citizens’ awareness in order to maintain and stabilize the status quo; • El-Oued Local Radio does not equally present the different viewpoints on the developmental topics. Although it receives guests with different opinions, the manner in which they deal with the discussion topics is subjected to particular agendas. This indicates their bias towards particular attitudes; • El-Oued Local Radio does not have an organism specializing in discussing developmental questions and topics, and that may provide developmental studies and programs that respect the specificity of the local environment; • El-Oued Local Radio’s developmental programs are not locally planned for because of the top-down policy of radio planning: from the central radio to the local radio. This explains that the person in charge of communication finds himself centrally monitored, which prevents him from discussing his local community’s topics; • The local Radio marginalizes the importance of feedback; this is reflected in its failure to rely on the local public as a source of information and its failure to open dialogue and interaction channels in its developmental programs, which hinders the active involvement of the public in the planning and implementation of the developmental programs.
أطروحة دكتوراء
Keywords: الإذاعة المحلية; التنمية المحلية; التخطيط الإذاعي; التفاعلية